Dissociative Disorders Interview Schedule, Portuguese version - Espirito-Santo, Helena (2018)
CHARACTERIZATION: The DDIS-P is a structured interview to assess the presence of dissociative, somatization, conversion disorders, borderline personality disorder, and major depression disorder in accordance with DSM criteria. STRUCTURE AND SCORING: The DDIS comprises 131 items for the diagnoses, and questions about childhood trauma, substance use, and sociodemographic information. There is no overall score, but rather the identification of a diagnosis according to whether it meets DSM criteria. PSYCHOMETRIC CHARACTERISTICS: Cohen's kappa was of 0.83. For the diagnosis of dissociative disorder, DDIS presented an overall efficiency of 89%. The probability of a dissociative patient being diagnosed as such (sensitivity) was 69% and the specificity was 91%.